The Responsibilities of Electronic Catalog System Providers for the Quality and Pricing of Goods/Services in Government Procurement - Sudarsono (Dinasti Research, 2025)
This study aims to identify, understand, and analyze the regulations governing electronic catalog system providers concerning the quality and pricing of goods/services in government procurement, as well as to determine the form of responsibility of electronic catalog system providers for the quality and pricing of goods/services in government procurement. The method used in this study is a normative juridical research method with a legislative approach and a legal concept analysis approach. The results of the study indicate that the regulation of electronic catalog system providers regarding the quality and pricing of goods/services in government procurement is governed by the Regulation of the National Public Procurement Agency (LKPP) Number 9 of 2021 on Online Stores and Electronic Catalogs in Government Procurement, which was further refined by the Decision of the Head of the National Public Procurement Agency of the Republic of Indonesia Number 122 of 2022, dated April 1, 2022. This regulation provides a more detailed explanation of the process for listing a product/commodity in the electronic catalog. The form of responsibility of electronic catalog system providers for discrepancies in the quality and pricing of goods/services in government procurement is that catalog providers are held accountable for any consequences arising from the low quality of products used by Ministries/Agencies/Local Governments. Therefore, if there is a difference between the quality and price listed in the electronic catalog and the actual product, the electronic catalog provider is responsible for compensating the losses incurred by the procuring party.